Analysis of Differences in Individual Characteristics, Lifestyle, Nutritional Status and Dieting Patterns in Pregnant Women with Preeclampsian History - Asti Melani Astari; Nurul Evi; Muladefi Choiriyah; Puji Ariyani; Anif Lailatul Fitriy (Journal of Nursing Science Update (JNSU), 2021)
Preeclampsia is a multisystem complication that occurs after 20 weeks of gestation. In recent years there has been no significant decrease in the incidence of preeclampsia, even in developed countries it is still the main cause of maternal and fetal morbidity and mortality. This study aims to analyze differences in individual characteristics, lifestyle (physical activity), nutritional status and diet in pregnant women with a history of preeclampsia. This research design is descriptive analytic with cross sectional approach. Samples were obtained from 55 pregnant women with consecutive sampling who met the inclusion criteria. Data analysis used chi-square test and spearman correlation test. The results showed a relationship between physical activity with systolic blood pressure (p value 0.001, r = 0.449) and diastolic (p value 0.43, r = 0.273), there was also a relationship between diet and risk factors for preeclampsia through blood pressure measurements as evidenced by increase in blood pressure (p value 0.000) in pregnant women in the working area of Puskesmas Kedungkandang Malang. The results of this study are expected to be used as a reference in intervening pregnant women at risk of preeclampsia, so that the disease does not develop more severely so that it does not endanger the lives of the mother and the fetus she is carrying.